2012
DOI: 10.1002/ijc.27356
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen G polymorphism is associated with an increased risk of invasive cancer of the uterine cervix

Abstract: Human leukocyte antigen (HLA)-G acts as negative regulator of the immune responses and its expression in tumor cells may enable them to escape immunosurveillance. The purpose of this study was to investigate the influence of HLA-G polymorphism on risk of high-grade cervical intraepithelial neoplasia (HG-CIN) and cervical cancer in a Canadian population. The authors have analyzed 1,372 women from participants recruited between 2001 and 2009 in the ongoing Biomarkers of Cervical Cancer Risk case-control study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 24 publications
3
45
1
2
Order By: Relevance
“…Another previous study in this cohort also found the HLA-G Ã 01:01:02 allele to be associated with both increased cumulative risk and persistence of HPV16 (28), and this allele was also recently linked to invasive cervical cancer (32). Both the HLA-G Ã 01:01:03 and HLA-G Ã 01:01:05 alleles associated with coinfections here were also previously found to be associated with increased odds of certain low-risk HPV infections in this cohort, but not among women purported to be highly exposed to HPV (28).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Another previous study in this cohort also found the HLA-G Ã 01:01:02 allele to be associated with both increased cumulative risk and persistence of HPV16 (28), and this allele was also recently linked to invasive cervical cancer (32). Both the HLA-G Ã 01:01:03 and HLA-G Ã 01:01:05 alleles associated with coinfections here were also previously found to be associated with increased odds of certain low-risk HPV infections in this cohort, but not among women purported to be highly exposed to HPV (28).…”
Section: Discussionsupporting
confidence: 66%
“…HLA alleles were typed from purified DNA obtained from cervical specimens collected at enrollment, using PCR amplification of sequence-specific primers for HLA-B (27,28). These HLA types were chosen a priori based on consistent published evidence to support their role in susceptibility to both HPV infection (27)(28)(29)(30) and cervical cancer (24,26,31,32).…”
Section: Hla Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…A few risk-modulating variants for cervical cancer have been identified by a candidate gene association study. The genes that are associated with cervical cancer susceptibility are involved in DNA repair, cell cycle and apoptosis, cell proliferation and differentiation, the human leukocyte antigen system, and various immune responses (Ferguson et al, 2012;Safaeian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Corroborando com estes achados, um importante estudo com a participação de 1.372 mulheres, sendo 833 controles saudáveis, 395 com HSIL e aumentado para desenvolvimento de ICC (P = 0,020) e o genótipo ins/ins está associado com a progressão de HSIL para ICC (OR = 2,0; IC = 1,01 -3,98; P = 0,048) (FERGUSON et al, 2012). Bertolotti e colaboradores sugerem que este mesmo genótipo possua associação com a progressão das lesões cervicais devido à ausência de ins/ins entre os casos de condiloma e sua presença aumentada entre as participantes com LSIL ou ICC (P = 0,011) (BERTOLOTTI et al, 2014).…”
Section: Análise Estatísticaunclassified